International code of phylogenetic nomenclature : (PhyloCode) - Cantino, Philip D.; De Queiroz, Kevin; International Society for Phylogenetic Nomenclature. Committee on Phylogenetic Nomenclature (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"This book will govern the names of clades, while species names will still be governed by traditional codes. PhyloCode is designed so that it can be used concurrently with the rankbased codes. It is not meant not to replace existing systems but to provide an alternative system for governing the application of both existing and newly proposed names"--
A new system for organizing and classifying living organisms. A phylogenetic code of biological nomenclature.
Ratified on January 20, 2019, by the Committee on Phylogenetic Nomenclature, of the International Society for Phylogenetic Nomenclature.
OCLC-licensed vendor bibliographic record.
Keywords: Biology -- Classification; Biology -- Nomenclature; Cladistic analysis; Phylogeny -- Nomenclature; Plants -- Phylogeny -- Nomenclature; NATURE / Animals; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / Evolution